2023
DOI: 10.1186/s12987-023-00454-z
|View full text |Cite
|
Sign up to set email alerts
|

Sizes and shapes of perivascular spaces surrounding murine pial arteries

Abstract: Background Flow of cerebrospinal fluid (CSF) through brain perivascular spaces (PVSs) is essential for the clearance of interstitial metabolic waste products whose accumulation and aggregation is a key mechanism of pathogenesis in many diseases. The PVS geometry has important implications for CSF flow as it affects CSF and solute transport rates. Thus, the size and shape of the perivascular spaces are essential parameters for models of CSF transport in the brain and require accurate quantificat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“… 21 , 53 PVS load has been supposed to be at a similar scale as the cerebral blood volume (CBV: 3%–5%) in the human brain, 9 which might be inferred from mice research where it has been shown a ratio of 1.12 to 1.88 between PVS to vessel cross‐sectional area. 54 Therefore, CSFF is a more PVS volume‐centered measure, while the DTI‐FW is an extracellular space–dominated measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 , 53 PVS load has been supposed to be at a similar scale as the cerebral blood volume (CBV: 3%–5%) in the human brain, 9 which might be inferred from mice research where it has been shown a ratio of 1.12 to 1.88 between PVS to vessel cross‐sectional area. 54 Therefore, CSFF is a more PVS volume‐centered measure, while the DTI‐FW is an extracellular space–dominated measure.…”
Section: Discussionmentioning
confidence: 99%
“…be inferred from mice research where it has been shown a ratio of 1.12 to 1.88 between PVS to vessel cross-sectional area. 54 Therefore, CSFF is a more PVS volume-centered measure, while the DTI-FW is an extracellular space-dominated measure.…”
Section: F I G U R Ementioning
confidence: 99%
“…First, models can serve as a generalized framework where data of different types and from distinct sources can be integrated to inform biological processes. For example, three different recent imaging and histological studies have reported direct measurements of the shapes and sizes of perivascular spaces at the pial surface [ 139 ], flow velocities within these perivascular spaces [ 66 ] and perivascular astroglial endfoot dimensions within the cortex [ 140 ], aspects that are anticipated to influence perivascular fluid and solute transport. While each study was conducted in isolation, and their results are not directly inter-relatable, computational models provide a medium for integrating these observations and understanding their respective and combined influences on fluid and solute transport along perivascular compartments.…”
Section: Perspectives For Future Research / Knowledge Gapsmentioning
confidence: 99%